As estratégias de responsabilização político-social da ANDI – Comunicação e Direitos nas políticas públicas de comunicação: o caso da Classificação Indicativa - Pinto, Rafaela Caetano (2018)
Public communication is per se a public interest. In this way, it should privilege the discussion about social issues that concern the promotion of citizenship. In thinking of this definition, it is understood that public communication is not strictly limited to the organs of public power, but to other organizations that, in the same way, have as their mission the defense of individual rights. Thus, we identify and select, as an empirical object, ANDI - Communication and Rights. It is a third sector organization and it performs the role of privileged social actor in the thematization of human rights and media. Among other areas of action, it defends the regulation of the media through deliberation of public communication policies (PCP), such as the Indicative Classification (IC), a case intentionally chosen in this study. In this way, it questions the role of the media as a field that must mobilize civil society, subject the public agenda, exercise accountability over State actions, and other functions. Thus, ANDI promotes actions with the State, in the form of theoretical inputs or direct incidence, in order to assist in the discussion of PCP. With the assumption that ANDI's performance goes beyond its media monitoring strategies, we identify its action through politico-social accountability strategies, especially in the case of the Indicative Classification (IC), supported by the concepts of social response (BRAGA, 2006) and media accountability systems (BERTRAND, 2002). Based on this context, we formulate, as a problem of this research: How do ANDI's political-social accountability strategies promote the discussion of public communication policies, as observed in the defense of the Indicative Classification? Thus, we propose, as a general objective: to analyze, from Indicative Classification, ANDI's political-social accountability strategies in the promotion and discussion of public communication policies. The empirical study was based on Depth Hermeneutics (THOMPSON, 2009) in which it was analyzed the ANDI performance in the implementation of the Indicative Classification system through data collected in interviews, in institutional documents and publications, and on the organization's website. Based on what was verified, ANDI's work is predominantly carried out through direct advocacy with the public authorities, as well as through its research related to the topic. We can infer that ANDI is an organization that has institutional legitimacy and specialized knowledge to develop political-social accountability strategies to act with the State in order to assist in the discussion of PCP to regulate the media field.